Base excess is associated with the risk of all-cause mortality in critically ill patients with acute myocardial infarction - Luo, Chaodi; Duan, Zhenzhen; Zheng, Tingting; Li, Qian; Wang, Danni; Wang, Boxiang; Gao, Pengjie; Han, Dan; Tian, Gang (Frontiers in Cardiovascular Medicine, 2022)
Background: Base excess (BE) represents an increase or decrease of alkali reserves in plasma to diagnosis acid-base disorders, independent of respiratory factors. Current findings about the prognostic value of BE on mortality of acute myocardial infarction (AMI) patients still unclear. We aimed to investigate the prognostic significance of BE on short-time all-cause mortality after AMI. Methods: We retrospectively examined 2465 patients who diagnosed with AMI in intensive care unit from the Medical Information Mart for Intensive Care III (MIMIC-III) database. We analyzed the association of BE with 28-day and 90-day all-cause mortality using multivariable Cox regression. We also utilized restricted cubic splines (RCS) to evaluate the relationship between BE and hazard ratio (HR). The primary outcome were 28-day and 90-day all-cause mortality. Results: When stratified according to quantiles, low BE is associated with higher 28-day and 90-day all-cause mortality. Multivariable Cox proportional hazard models revealed that low BE was an independent determinant of 28-day all-cause mortality (HR 4.158, 95% CI 3.203-5.398 (low versus normal BE), HR 1.354, 95% CI 0.896-2.049 (high versus normal BE)) and 90-day all-cause mortality (HR 4.078, 95% CI 3.160-5.263 (low versus normal BE), HR 1.369, 95% CI 0.917-2.045 (high versus normal BE)), even after adjustment for significant prognostic covariates. The results were also consistent in subgroup analysis. RCS revealed that BE and all-cause mortality was “L” type for 28-day and 90-day mortality, as well as adjusting for covariates. Furthermore, regarding mortality stratified by BE and carbon dioxide partial pressure (PaCO2), patients with low BE (<3.5 mEq/L) and high PaCO2 (>45 mmHg) had the highest mortality compared with other groups. Conclusion: Our study revealed that low BE was significantly associated with 28-day and 90-day mortality in AMI patients and indicated the value of stratifying the mortality risk of AMI patients by BE.